Pengaruh Konsentrasi Auksin pada Pertumbuhan Bibit Vanili (Vanilla planifolia A.) - Rona Aditania; Yan Sukmawan; Made Same; Adryade Reshi Gusta (Fakultas Pertanian, Universitas Timor, 2023)
Indonesia is one of the world's most enormous vanilla (Vanilla planifolia A.) producing countries. Propagation of vanilla plants by vegetative means using cuttings consisting of 1-3 segments, each node of vanilla has the potential to remove roots and shoots so that with this potential, it is possible for vanilla to be propagated by cuttings. Still, the growing ability is meagre, so special treatment is needed by giving plant growth regulators (PGR). Information regarding using NAA on the growth of vanilla cuttings has not been found. Therefore, this study was conducted to obtain the best NAA concentration for the growth of vanilla seedlings. This research was carried out from July - November 2021 in the experimental garden of the Politeknik Negeri Lampung. The method used was a single factor Randomized Block Design (RBD) with five treatments and five replications, so there were 25 experimental units. The treatment consisted of five levels, namely 0 ppm (R0), 100 ppm (R1), 200 ppm (R2), 300 ppm (R3), and 400 ppm (R4). The data was analysed using the F test. If there is a difference, proceed with the HSD test at the 5% level. The results showed that the 200 ppm (R2) NAA concentration gave the highest average value for several variables, namely, shoot height (16.86 cm), number of leaves (4.68), number of internodes (4.84), and root length (57.05 cm) at the age of 30 DAP to 120 DAP.